Studi Penggunaan Beban Pada Gardu Distribusi Penyulang RRI PT. PLN (Persero) ULP Fakfak - Yulianto La Elo; Naomi Lembang; Irsul Tardi (Pusat riset dan Inovasi Nasional, 2022)
In the process of distributing electricity from the generator to the consumer, it goes through many processes and passes through several parts. Starting from the electric power distribution system, one of which is the distribution system. Considering that the scope of this distribution network is directly related and is located in an inhabited area, in addition to meeting technical quality requirements, it must also meet the requirements for being safe for users and familiar with the environment. In this distribution system there is a very important equipment in distributing electric power, namely the distribution substation. Because of the important role of the distribution substation, it must be protected from disturbances that may occur. One of them is the load imbalance between phases. In practice and in reality, in various locations of electric power distribution, a completely balanced load condition is obtained, mainly because of the large number of single-phase load groups that are serviced by a low-voltage three-phase distribution system. This is because the characteristics and types of electrical power user equipment vary with different consumer conditions and activities. To obtain load balance, load balancing is carried out between phases for load distribution so that load adjustments occur at distribution substations.